Psychosocial Factors Associated with Anxiety and Delivery Pain - Nisa, Shofia Maharani Khoirun; Qadrijati, Isna; Murti, Bhisma (Journal of Maternal and Child Health, 2018)
Background: Anxiety and pain are physiologic symptoms experienced by mothers during birth delivery. However, if these symptoms are not well-managed they can cause low birth weight, prematurity, prolonged labor, and postpartum depression. This study aimed to analyze the psychosocial factors associated with anxiety and delivery pain. Subjects and Method: This was an analytical observational study with cross sectional design. The study was conducted at Gajahan community health center, Surakarta Hospital, and Muhammadiyah Hospital, Delanggu, Central Java, from December 2017 to January 2018. A total sample of 166 delivery mothers were selected for this study by purposive sampling. The dependent variables were anxiety and delivery pain. The independent variables were parity, psychological stress, coping mechanism, family income, and family support. The data were collected by questionnaire. Anxiety was measured by modified Preg